O-016 Variability of sperm DNA fragmentation in a longitudinal trial of intrauterine inseminations. (30th June 2022) - Peeters, K; Punjabi, U; Roelant, E; Goovaerts, I; Van Mulders, H; De Neubourg, D
Abstract: Study question: Does variability in sperm DNA fragmentation (SDF) follow that observed in standard semen parameters and is this linked to outcome results? Summary answer: Variability in SDF and in semen parameters is comparable but live birth rate tends to be lower in men with repetitive high SDF. What is known already: Environmental, technical and biological factors are implicated in the intra-individual variability observed in routine semen parameters. This variation is not observed in SDF testing using the sperm chromatin structure assay. Most laboratories undertake SDF testing on one semen sample, assuming that one single measurement represents the patient's condition and is both stable and associated with a good diagnostic value. Most variability observed in SDF tests relies essentially on paired observations with a short or long time interval between test and retest. Study design, size, duration: A monocentric, prospective cohort study was conducted October 2017 - October 2020. Couples with a mild or unexplained male infertility initiated a natural cycle IUI protocol until pregnancy was achieved for a maximum of four cycles. 313 semen samples from 112 men were analyzed for SDF before and after semen preparation. This work was supported by the Fonds Wetenschappelijk Onderzoek (FWO), Research Foundation Flanders (grant number T007016N). Participants/materials, setting, methods: Semen samples were analyzed and prepared by density gradient centrifugation. SDF was assessed via TUNEL assay before and after preparation. Clinical pregnancies and live births were registered. Intraclass Correlation Coefficients (ICC) were used to estimate the intra- and inter-variability. Main results and the role of chance: The ICC for SDF (0.33 in the ejaculate, 0.54 after density gradient) and semen variables (0.42-0.62) were comparable. These values mean considerable intra-individual variation, both for semen variables and for SDF variables. Using fertile threshold SDF values (13% before and 8% after density gradient), 3 patient groups were distinguished: 13.4% of men showed high SDF in all ejaculates, 58.0% always showed low SDF and 28.6% fluctuated between the two during the trial. After density gradient more patients were found in the High group (42.3%) and less patients in the Low group (26.1%), while the proportion of Fluctuaters remained constant (31.5%). Most (66.7%) men with high SDF retain their high SDF after gradient, and also 56.3% of the Fluctuaters react with a high SDF after gradient. The Low SDF category, on the contrary, distributes itself evenly between the three categories after gradient. In the 112 couples, 26 (23.2%) clinical pregnancies were obtained with 21 (18.8%) live births. The live birth rate for the High, Fluctuaters and Low groups was 6.7%, 18.8% and 20.0% for ejaculate SDF and 12.8%, 20.0% and 27.6% for SDF after density gradient. These differences however did not reach significance (chi-square testing, p > 0.05). Limitations, reasons for caution: Our results need to be substantiated and opportunities created to explore populations with an extreme male factor and the clinical implications in different assisted reproductive techniques. Wider implications of the findings: SDF testing provides additional information and helps identify causes otherwise missed with traditional semen analysis alone. One out of 3 patients fluctuate in their SDF values. A second SDF testing is advocated to isolate these fluctuaters. The detection of DNA damage after semen preparation is indispensable for therapeutic purposes. Trial registration number: NCT03319654